INFORMING INTERVENTIONS: THE IMPORTANCE OF CONTEXTUAL FACTORS IN THE PREDICTION OF SEXUAL RISK BEHAVIORS AMONG TRANSGENDER WOMEN - Sevelius, Jae M. (AIDS Educ Prev, 2009)
This study identifies contextual factors that predict risky sexual behavior among 153 transgender women who participated in a structured survey soliciting information on demographics, substance use, HIV status, risk behaviors, and other health and psychosocial factors. Multivariate logistic regression models were used to determine predictors. Inconsistent condom use was associated with stimulant use, unstable housing, and recruitment site. Substance use during sex was associated with unstable housing and stimulant use. Sex work was associated with hormone use, gender confirming surgeries, and younger age. When developing interventions for transgender women, it may be useful to focus on predictors of risk behavior rather than predictors of current HIV status (i.e., race/ethnicity as “risk factor”), because these behaviors are the target of interventions aimed at sexual risk reduction. Implications include potential benefits of context-specific interventions, structural interventions addressing barriers to housing and health care, and culturally specific substance abuse treatment programs for transgender women.